1992
DOI: 10.1007/bf00145332
|View full text |Cite
|
Sign up to set email alerts
|

Features of cholera and Vibrio parahaemolyticus diarrhoea endemicity in Calabar, Nigeria

Abstract: The clinical and epidemiological features of acute vibrio diarrhoeal disease were studied in 881 patients seen at the University of Calabar Teaching Hospital (UCTH), Calabar, Nigeria, between January and December 1989. Stools and rectal swabs of patients and randomly-selected control subjects were microscopically and culturally examined for the presence of enteric pathogens. Households of vibrio diarrhoea cases and matched controls were visited for ecologic studies. Of a total of 108 (12.3%) culturally-confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 11 publications
1
13
1
Order By: Relevance
“…The three species of Vibrio, namely, V. cholerae, V. parahaemolyticus and V. alginolyticus, isolated from the environment are known human pathogens and the first two have been associated with clinical conditions and environmental contamination in the region (Utsalo et al 1992, Eko et al 1994. The work reported here further provides the relative numbers of the Vibrio, even at different seasons.…”
Section: Discussionmentioning
confidence: 99%
“…The three species of Vibrio, namely, V. cholerae, V. parahaemolyticus and V. alginolyticus, isolated from the environment are known human pathogens and the first two have been associated with clinical conditions and environmental contamination in the region (Utsalo et al 1992, Eko et al 1994. The work reported here further provides the relative numbers of the Vibrio, even at different seasons.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Vibrio includes many harmless species, natives of fresh, brackish and marine waters and is an important component of the aquatic microbial communities (Colwell & Huq, 1994), also able to persist in shellfish. Among these should also be mentioned some etiologic agents of enteric diseases and epidemics (Faruque et al , 1998; Sechi et al , 2000; Gil et al , 2004): O1 and O139 serotypes of Vibrio cholerae , some V. cholerae non‐O1 serotypes (Thungapathra et al , 2002), Vibrio parahaemolyticus (Utsalo et al , 1992), Vibrio fluvialis (Ahmed et al , 2004) and Vibrio alginolyticus (Ripabelli et al , 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall [7,26,30,32,45,62] and temperature [7,26,50] were identified as primary climatic drivers of cholera transmission in Nigeria. The association between cholera outbreaks and climatic drivers, particularly seasonal tropical rainfall, is well documented in other contexts [63][64][65][66].…”
Section: Interpretation Of Key Findingsmentioning
confidence: 99%
“…Eight studies [12,17,24,32,41,50,70,75] found the potential role of health systems-related factors in driving the transmission of cholera in Nigeria. Regarding health service delivery, evidence centred on inadequate and inefficient surveillance system, as well as inadequate laboratory diagnostic capacity; in addition, poor technical capacity of health workers to manage cholera cases, especially in rural areas.…”
Section: Interpretation Of Key Findingsmentioning
confidence: 99%